Sketching theory: Introducing the pictorial format - Smith, Maarten; van der Zwan, Sander; van Dijk, Ludger; Bruineberg, Jelle; Hummels, Caroline (Journal of Human-Technology Relations, 2023)
The Journal of Human-Technology Relations is committed to investigating human-technology relations from a wide range of academic disciplines and subdisciplines in the humanities and social sciences, from design to philosophy and everything in between. To provide a space for productive correspondence with these practices the journal offers authors the possibility to submit pictorials. Pictorials take seriously the mutually constitutive relation between material process and product. They are papers in which visual components (e.g. diagrams, sketches, illustrations, renderings, photographs, annotated photographs, gifs) play an important role. At a minimum, these visuals do more than support the text. At their best, they work together with the text in a way that makes meaning irreducible to either medium alone. In this pictorial we demonstrate this scope by example, making a philosophical argument with more than textual means.